Service offshoring and firm employment - Peter S. Eppinger (University of Tübingen, Faculty of Economics and Social Sciences, 2017)
Major technological advances have recently spurred a new wave of offshoring in services, which used to be non-tradable. Should service workers in developed countries worry about their jobs? Trade theory has given a nuanced answer to this question, suggesting that efficiency gains from offshoring may counteract direct job losses, which leaves the predicted net effect ambiguous. This paper investigates the employment effects of service offshoring in a newly combined and exceptionally detailed panel dataset, covering almost the entire universe of German firms' service imports over the years 2002-2013. It exploits firm-specific export supply shocks by partner countries and service types as an instrumental variable to find that service offshoring has increased firm employment. In line with the canonical trade in tasks model, the employment gains are greater in firms with higher initial levels of service offshoring.
urn:nbn:de:bsz:21-dspace-781918
Keywords: F16; F66; F14; J23; 330; service offshoring; employment; firm-level data; service trade; trade in tasks